Factors impeding the successful implementation of corporate Governance reform measures in ZIMBABWE: A case study of NRZ - Shumbaimwe, M (BUSE, 2022)
The goal of this study was to see how corporate governance issues affect the image of state-owned businesses. To address this issue, the researcher devised the following goals: to determine the current state of corporate governance practices in SOEs, using NRZ as a case study; to identify corporate governance challenges affecting the corporate boards of SOEs, using NRZ as a case study; to determine the current state of corporate governance practices in SOEs, using NRZ as a case study; to assess the impact of political interference on SOEs' corporate image, using NRZ as a case study; to investigate the impact of directors' conflicting interests on SOEs' corporate image, using NRZ as a case study; and to identify potential remedial strategies to address the corporate governance challenges prevailing in SOEs' corporate boards, using NRZ as a case study. In order to answer the research questions based on corporate governance outlined in chapter one, the literature focused on theoretical and empirical data. For explanation of technical aspects of corporate governance, the perspectives of various academics and authors were scrutinized, and the literature under evaluation was sourced from journal articles, textbooks, and the internet. According to Bryman et al (2007), the Positivism paradigm holds the prospect that human errors, behaviors, and institutions can be evaluated as objectively as the natural world. Concepts may be quantified, postulated, and aims can be measured thanks to positivism. Primary data on the influence of corporate governance difficulties on corporate image in state-owned firms was collected using questionnaires. Because the data was original and directly from the respondent, the veracity of the material could be easily checked. The agency problem coming from the separation of ownership and control was shown to be the cause of corporate governance complications for state-owned firms in this study. The study also proposed potential solutions to these problems, including the adoption of International Public Sector Accounting Standards (IPSASs) and the establishment of incentive programs, among others.
Keywords: corporate governance; state owned; SOCIAL SCIENCES::Business and economics